Dysphagia - New Advances 2022
DOI: 10.5772/intechopen.101799
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Following Anterior Cervical Spine Surgery

Abstract: Dysphasia is regarded as one of the common complications following anterior cervical discectomy and fusion, the reported incidence varies widely and is depending on several factors, such as smoking, multi levels, anterior plating, we will discuss historical review, pathogenesis, epidemiology, clinical presentation including presentation including perioperative and postoperative recommendation and will end up with different stops and tricks to decrease this complication, in each topics we will review the eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Further, the reported ACDF complications include stenosis of the respiratory tract by swelling of the surrounding tissue, swallowing disturbance, and hoarseness due to traction of the vocal cord [16]. Meanwhile, the aftermath of laminoplasty surgery complications can lead to persistent neuropathic arm pain, axial neck pain, and a decline in cervical alignment, primarily caused by the advancement of kyphosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the reported ACDF complications include stenosis of the respiratory tract by swelling of the surrounding tissue, swallowing disturbance, and hoarseness due to traction of the vocal cord [16]. Meanwhile, the aftermath of laminoplasty surgery complications can lead to persistent neuropathic arm pain, axial neck pain, and a decline in cervical alignment, primarily caused by the advancement of kyphosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking: Smoking contributes to many complications in the postoperative setting after cervical spine surgery including dysphagia as reported in multiple studies for patients undergoing ACSS. 6 For example, Hasan et al reported a greater incidence of dysphagia in smokers (51%) compared with nonsmokers (28%) in their study of 165 patients who underwent ACSS. Lateral radiograph (A) and sagittal CT scan (B) of a patient with chronic dysphagia due to plate prominence; the patient also had C7-T1 pseudarthrosis.…”
Section: Preoperativementioning
confidence: 96%
“…14,16 Pathophysiology Dysphagia occurs when swallowing or deglutition is interrupted by neural, muscular, and/or mucosal abnormalities. 6,16 This complex process requires voluntary and involuntary responses that enable coordination of both swallowing and breathing. Deglutition is often divided into an oropharyngeal phase and esophageal phase.…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations